2019
DOI: 10.3389/fcimb.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Whole-Transcriptome RNA Expression in MDCK Cells Infected With the H3N2 and H5N1 Canine Influenza Viruses

Abstract: This study aimed to detect changes in the complete transcriptome of MDCK cells after infection with the H5N1 and H3N2 canine influenza viruses using high-throughput sequencing, search for differentially expressed RNAs in the transcriptome of MDCK cells infected with H5N1 and H3N2 using comparative analysis, and explain the differences in the pathogenicity of H5N1 and H3N2 at the transcriptome level. Based on the results of our comparative analysis, significantly different levels of expression were found for 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Compared with the circRNA-miRNA-mRNA network in Madin-Darby Canine Kidney (MDCK) cells infected with influenza A/H3N2, our network in MERS-CoV-infected Calu-3 cells demonstrated a higher number of DE circRNAs (7 vs 3), miR-NAs (19 vs 1), and mRNAs (547 vs 9). This might imply that MERS-CoV infection induced a more profound and global change in the host ceRNA network compared to the less virulent influenza A/H3N2, although the differences in experimental set up should also be considered [14]. The DE circRNAs in our network were associated with a wide range of biological, cellular, and molecular processes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with the circRNA-miRNA-mRNA network in Madin-Darby Canine Kidney (MDCK) cells infected with influenza A/H3N2, our network in MERS-CoV-infected Calu-3 cells demonstrated a higher number of DE circRNAs (7 vs 3), miR-NAs (19 vs 1), and mRNAs (547 vs 9). This might imply that MERS-CoV infection induced a more profound and global change in the host ceRNA network compared to the less virulent influenza A/H3N2, although the differences in experimental set up should also be considered [14]. The DE circRNAs in our network were associated with a wide range of biological, cellular, and molecular processes.…”
Section: Discussionmentioning
confidence: 94%
“…circRNAs possess miRNA-sponging activity and counteract the miRNA's inhibitory activity on the target mRNA [6,7]. Recent studies showed that the expressions of circRNAs were perturbed in viral infections caused by both DNA (hepatitis B virus, Kaposi's sarcomaassociated herpesvirus, and simian vacuolating virus 40) and RNA [Ebola virus, porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), influenza A viruses, and avian leukosis virus subgroup-J] viruses [8][9][10][11][12][13][14][15], and that these cir-cRNAs might serve as potential antiviral targets [9,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, H5N1 viruses may induce the expression of a distinct profile of host genes, altering the cellular landscape. Comparison of the global transcriptome upon H1N1, H3N2, or H5N1 virus infection has revealed significant differences in host gene expression and host proteomic responses between these strains (50,51). Thus, H5N1 virus infection may reshape the cellular milieu to promote a host factor environment that enables productive replication in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…They further showed that this inhibition occurs independent of translation factor eIF4A3, a factor that is essential in the execution of NMD (circPSD3 RNA harbors six predicted eIF4A3 binding sites). Interestingly, circPSD3 also exerts a similar pro-viral effect in dengue virus but not in Chikungunya virus-infected cells, suggesting distinct effects on different Lastly, RNA-seq data analysis of cells infected with other viruses such as porcine endemic diarrhea virus (PEDV) [72], grass carp reovirus [73], avian leukosis virus [74], simian virus 40 (SV40) [75], transmissible gastroenteritis virus (TGEV) [76] and canine influenza viruses [77], has also revealed host circRNAs changes upon virus infection. The potential function of these host circRNAs has been predicted based on GO enrichment and KEGG pathway analysis, as well as by the concept of ceRNA networks.…”
Section: Accepted Articlementioning
confidence: 99%